Translocation t(1;19) in acute precursor B-cell lymphoblastic Leukaemia in paediatric patients- Pakistani population - Rehman, Palwasha; Romena Qazi; Muhammad Hammad-ur-Rehman (Journal of the Pakistan Medical Association, 2022)
Objective: To determine the impact of translocation t(1;19) in paediatric patients diagnosed with precursor B-cell acute lymphoblastic leukaemia. Methods: The retrospective study was conducted at the Shaukat Khanum Memorial Cancer Hospital and Research Centre, Lahore, Pakistan, and comprised data from January 2012 to January 2018 of paediatric patients diagnosed with precursor B-cell acute lymphoblastic leukaemia. Data of patients having t(1;19) translocation with or without complex karyotype formed group A, while data of patients without any cytogenetic abnormality formed the control group B. Relapse and event-free survival were calculated and the outcomes were compared between the groups. Data was analysed using SPSS 20. Results: Of the 450 subjects whose data was analysed, 84(18.7%) were included; 25(30%) in group A and 59(70%) were in group B. There were 21(84%) males and 4(16%) females in group A with mean age on presentation 3.68±0.6 years compared to 41(69.4%) males and 18(30.5%) females with mean age on presentation 4.0±0.92 (p>0.05). There were no differences between the groups in terms of baseline markers (p>0.05). The relapse and event-free survival rates were also not significantly different between the groups (p>0.05). Conclusion: There was no significant difference related to outcomes of precursor B-cell acute lymphoblastic leukaemia patients having t(1;19) translocation with or without complex karyotype and those without any cytogenetic abnormality, indicating that translocation t(1;19)-positive patients do not need treatment intensification. Key Words: Acute Pre-B ALL, Children, t (1;19), Oncoprotein E2A-PBX1.